Factors Affecting The Giving Of Mp-Asi To Infants At The Pratama Hanna Kasih Clinic Year 2022 - Fransysca, Helena; Manurung, Nurdiana (Jurnal EduHealth, 2022)
MP-ASI is food that is given together with breast milk until the age of 2 years. Giving mother's milk substitute (PASI) to children aged before 6 months is not recommended because it can increase the risk of disease, especially diarrhea. There are 30.2% of babies who get exclusive breastfeeding and babies who get MP-ASI as much as 69.8% of the total babies in Indonesia. The sampling technique was Total Sampling with the following sample criteria: Mothers who had babies under or equal to 2 years (24 months), the sample in this study was 30 people. The results of statistical tests using the Chi-Square test showed that the relationship between mother's knowledge in giving MP-ASI to infants had good knowledge of 8 respondents (47.1%). Employment relations with giving MP-ASI to infants are the majority of mothers who do not work as many as 19 respondents (63.3%), and socio-cultural relations with providing MP-ASI to infants is the majority of mothers who have good socio- culture as many as 22 respondents (73.3%). The results of an analysis of the factors that influence the provision of MP-ASI to babies at the Hanna Kasih Primary Clinic in 2022 from 17 respondents (56.7%) who have good knowledge, this is closely related to preventing early complementary feeding. There were 19 respondents (63.3%) who did not work, this was because working mothers only had a small period of time off from work and 22 respondents (73.3%) had good socio-culture, this was because the influence of customs could affect the pattern of giving Early MP-ASI in infants. and socio-cultural relations with providing MP-ASI to infants is the majority of mothers who have good socio-culture as many as 22 respondents (73.3%). The results of an analysis of the factors that influence the provision of MP-ASI to babies at the Hanna Kasih Primary Clinic in 2022 from 17 respondents (56.7%) who have good knowledge, this is closely related to preventing early complementary feeding. There were 19 respondents (63.3%) who did not work, this was because working mothers only had a small period of time off from work and 22 respondents (73.3%) had good socio-culture, this was because the influence of customs could affect the pattern of giving Early MP-ASI in infants. and socio-cultural relations with providing MP-ASI to infants is the majority of mothers who have good socio-culture as many as 22 respondents (73.3%). The results of an analysis of the factors that influence the provision of MP-ASI to babies at the Hanna Kasih Primary Clinic in 2022 from 17 respondents (56.7%) who have good knowledge, this is closely related to preventing early complementary feeding. There were 19 respondents (63.3%) who did not work, this was because working mothers only had a small period of time off from work and 22 respondents (73.3%) had good socio-culture, this was because the influence of customs could affect the pattern of giving Early MP-ASI in infants. The results of an analysis of the factors that influence the provision of MP-ASI to babies at the Hanna Kasih Primary Clinic in 2022 from 17 respondents (56.7%) who have good knowledge, this is closely related to preventing early complementary feeding. There were 19 respondents (63.3%) who did not work, this was because working mothers only had a small period of time off from work and 22 respondents (73.3%) had good socio-culture, this was because the influence of customs could affect the pattern of giving Early MP-ASI in infants. The results of an analysis of the factors that influence the provision of MP-ASI to babies at the Hanna Kasih Primary Clinic in 2022 from 17 respondents (56.7%) who have good knowledge, this is closely related to preventing early complementary feeding. There were 19 respondents (63.3%) who did not work, this was because working mothers only had a small period of time off from work and 22 respondents (73.3%) had good socio-culture, this was because the influence of customs could affect the pattern of giving Early MP-ASI in infants.